Hubungan Asupan Protein dan Zink dengan Kejadian Stunting pada Anak Balita - Hawani, Ikat Tri; Suryani, Desri; Natan, Okdi; Meriwati, Meriwati (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2024)
tunting in Indonesia based on data from the 2024 Indonesian Nutrition Status Survey (SSGI) states that it continues to decline every year from 2021 – 2023 (24.4% - 17.8%). This figure is still below the target of achieving a reduction of 3.8% per year. In 2023, in the city of Bengkulu, out of 20 community health centers, 14 other community health centers will have cases of stunting with the highest incidence being in the Sawah Width community health center. This research determines the relationship between protein and zinc and the incidence of stunting in children under five in the Sawah Lebar Community Health Center Working Area, Bengkulu City. The research design used a cross-sectional approach. The sample used for stunting toddlers in the Sawah Width Community Health Center working area was 96 people. The sampling technique uses Simple Random Sampling. The data analysis used in this research is univariate analysis which can be used to determine the distribution of intake for each variable studied, namely protein and zinc intake, analysis using the chi-square statistical test. The results of this study show that most of the characteristics of stunting incidents are female (59.4%), toddlers are categorized as stunted (30.2%), protein intake is in the excessive category (83.3%), zinc intake is in the sufficient category (44.2%). There is a relationship between zinc intake and the incidence of stunting in children under five in the Sawah Lebar Community Health Center Working Area, Bengkulu City. There is no relationship between protein intake and the incidence of stunting in children under five in the Sawah Lebar Community Health Center Working Area, Bengkulu City.